A Study on Student’s Learning Achievement with Traditional Assessment and Portfolio Assessment. - Sarifuddin Muhamad (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
Abstack:The purposes of this research are to describe the student’s learning achievement with traditional assessment and portfolio assessment, and then find out the difference between the student’s learning achievement with traditional assessment and portfolio assessment. The design of this research is ex post facto. The population is the 1st class of students of MTs Muamalah Jurang Jaler. In selecting the sample is used clustered random sampling. The students of class 1A and 1B of MTs Putri Al- Islahuddiny Kediri are chosen as the sample. The data collection is done by observation and collecting the documentation. T-test is used to analysis the difference between the students’ learning achievement with traditional assessment and portfolio assessment. Based on the analysis, the researcher finds that mean of the class with traditional assessment is 60.00 and mean of the class with portfolio assessment is 70.31. By using t-test at the level of significance (a) 0.05, is got tratio is bigger than ttable, that is tratio = 2.833 > ttable = 1.992, it shows that there is a significant difference between the students’ learning achievement with traditional assessment and portfolio assessment. It can be concluded that the student learning achievement with portfolio assessment is better than the student learning achievement with traditional assessment at the level of believe 95%. But portfolio assessment is better implemented in small class because teacher will be easier in managing the class. Key term: Traditional Assessment and Portfolio Assessment.